A note on the collection of associated behavioural data with biopsy samples during cetacean assessment cruises - L. Mesnick, Sarah; Clapham, Phillip; E. Dizon, Andrew (J. Cetacean Res. Manage., 1999)
Understanding the influence of social organisation on the distribution, abundance and genetic structure of cetacean populations is critical in developing better predictive models for management. Field data on cetacean social organisation are far more valuable when collected and analysed together with genetic data from biopsy samples and environmental information (e.g. oceanographic patterns, prey availability). Traditionally, however, studies of cetacean social behaviour and studies of cetacean population dynamics have been conducted independently (Tillman and Donovan, 1986). To integrate these fields, this paper recommends that multi-disciplinary cetacean assessment surveys collect biopsy and associated behavioural data for each sample taken (the minimum data being group size, number of animals biopsied and age class). Examples of sampling forms, outlining the desired information, are provided. Understanding of cetacean stock structure and the processes affecting stock differentiation will best come from a combined genetic, social, ecological and oceanographic approach.